advocacy dimension in the US-Israel strategic alliance (Journal of the College of Basic Education, 2023)
The United States has enduring interests in the Arab region. The birth of her family is that this areaIt is the source of energy and lifeblood, it developed a special strategy based on two principlesEssentials are:Israel's security protection.- Ensuring the flow of oil wealth to its outlets in the United States.Based on this, the United States had to build an advanced base for it in the region.Ensure that these two principles are compatible and sometimes parallel. American policy planners have taken care of itStrategic relations with Israel are growing steadily and expanding vertically and horizontally according to the influence ofPro-Israel public opinion within organized groups in the United States has risenGradually, it reached the level of a strategic alliance.It is certain that the influence of US domestic policy has cast a shadow, according to the foregoing.on the Arab-Israeli conflict, based on the fact that the Americans sympathize withThey sympathize with Israel more than they sympathize with the Arabs in general. American Jews areCompletely loyal to Israel, however, non-Jewish Americans also tend to support Israel.It was less than enthusiastic (1). The policy and propaganda tools play an active and effective role inHe forced the US administration and Congress to take pro-Israel decisions on a large scale.The press of all kinds reflects this trend, as news and analysis of Israel are published.While the news about the Arabs did not receive much of the interest of the workers.in this page. Usually, advertising coverage takes the form of stereotypes that show